The Right Place. Human resources and labour policies for Italy, R. Benini and F. Dafano, Eurilink University Press, 2020 - Martini, Sara; Blasetti, Margherita (Community Notebook. People, Education and Welfare in the Society 5.0, 2023)
Il Posto Giusto. Risorse umane e politiche del lavoro per l’Italia (Human resources and labour policies for Italy) is the title of the book written by Romano Benini and Fabrizio Dafano after considerable work on the evolutionary analysis of the world of work at a global level, with particular reference to the national framework. Defining the intent of the work will prove to be a difficult and very limited undertaking, if one attempts to enclose it within a few lines: indeed, it is a far-reaching objective and not without a certain audacity, like all the greatest human works. The authors, reflecting on the most recent social, work and organisational panorama, propose to open up new avenues, or rather ‘new ideas and new forms of organisation, more responsive to the needs of truth and the enhancement of intelligence, which are priority dimensions with respect to legitimate expectations concerning professional and budgetary performance’ (Benini and Dafano, 2020: 109).